Comparison of Chess Engines: A Review - Singh, Rajesh Kumar; Negi, Satish Kumar; Chandra, Pusphendra Kumar (International Journal of Computer Sciences and Engineering, 2025)
The Chess engine alludes to a program that examines chess and chess variation positions. The first ever chess engine to have won against a human grandmaster was IBM’s DeepBlue in 1999. Since then multiple chess engines have emerged with improved search heuristics, hardware sets and dictionaries. Though in recent years many chess engines with a machine learning approach have produced striking achievements in comparison to the typical bruteforce chess engines. This paper aims to review the selected chess engines which generate counter moves automatically. Their respective specialties will be explained and compared to give insight on direction of research on chess game in modern world